Centenary book (1920-2020) - Luis A, Carriquiry; Francisco, Crestanello; Armando, Lanfranconi; Hugo, Maglione; José P., Perrier; Alberto, Piñeyro (Cirugía del Uruguay, 2020)
As part of the celebration of its 100th anniversary, the Uruguayan Surgical Society has published a book that compiles its history, a centennial account of its scientific and professional activity, highlighting the personalities who marked milestones in the country's surgery.